International Evidence on Cost, Revenue, and Profit Efficiency of Conventional and Islamic Banks - I. Bader, Mohammed Khaled (2007)
Bank efficiency is important in achieving the competitive edge for survival in a globalised banking industry. Conventional and Islamic banks operate on different principles in maximizing the wealth of their shareholders and are subjected to the competitive regulatory environment. Minimising cost and maximising revenues and profits to ensure survival are the two aims of all banks. These aims ensure the efficiency of financial sector and contribute to the overall economic growth. An important issue that needs to be addressed is the differences in the level of efficiency of these banks. In spite of the overwhelming empirical evidence on the efficiency of conventional banks, to date, there is no comprehensive evidence on the comparative cost, revenue, and profit efficiency of conventional and Islamic banks. This study fills this gap by analysing and comparing the efficiencies of Islamic and conventional banks in 21 countries during the period 1990-2005 The cost, revenue, and profit efficiency of Islamic banks and conventional banks are analyzed based on size, age, and region. The average and over-time efficiency for these banks are analyzed using Data Envelopment Analysis (DEA) and Financial Ratios. Overall cost and profit efficiencies are ascertained using the Stochastic Frontier Approach (SFA). The findings suggest that there are no significant differences between the overall efficiency results of conventional and Islamic banks irrespective of the method of analysis. Based on the documented evidence on efficiency of conventional banks, these findings imply that the banking transactions compliant with the Shari'ah are not an impediment to efficiency of Islamic banks. However, there is a substantial avenue to fhther improve the cost, revenue and profit efficiencies in both the banking systems. The DEA based findings show no significance difference in average efficiency scores between big and small banks and between new and old banks in both the banking streams. However, geographical location explains the significant differences in revenue and profit efficiency. Further, the results show that, on average, banks are better in utilising their resources than in generating revenues and profits. In general, more inefficiency comes from the revenue side and banks in both banking streams need to further improve their revenue efficiency. The evidence, based on SFA, suggests no significant differences between the cost and profit efficiency scores between conventional and Islamic banks based on size, age, and region. Similar evidence is observed from the Financial Ratios analysis.Overall, the results on the efficiency of conventional and Islamic banks are consistent with the documented literature. The robustness of the results has been tested based on single-&untry analysis and dso a group of seIe&ted countries representing relatively less-developed and more-developed countries. Except for minor differences the results of these tests are consistent with the overall results, further substantiating the fact that there are no significant differences in cost, revenue and profit efficiency of conventional and Islamic banks.